Occupational cold exposure is associated with upper extremity pain - Stjernbrandt, Albin; Pettersson, Hans; Wahlström, Viktoria; Wahlström, Jens; Lewis, Charlotte (Frontiers in Pain Research, 2023)
Background: Occupational cold exposure is common in Sweden but potential impacts on musculoskeletal disorders have not been thoroughly investigated. The primary aim of this study was to determine the associations between occupational contact and ambient cooling in relation to pain in the upper extremity. Methods: In this cross-sectional study, a digital survey was conducted on a population-based sample of women and men between 24 and 76 years of age, living in northern Sweden. Occupational cold exposure, heavy manual handling, work with vibrating tools as well as the presence of upper extremity pain at different sites were subjectively reported. Associations between exposure and outcome were evaluated using multiple binary logistic regression. Results: The final study sample included 2,089 (54.4%) women and 1,754 men, with a mean age of 56 years. Hand pain was reported by 196 (5.2%), lower arm pain by 144 (3.8%), and upper arm pain by 451 (11.9%). Severe ambient cooling for more than half of the working time was statistically significantly associated with hand pain (OR 2.30; 95% CI 1.23–4.29) and upper arm pain (OR 1.57; 95% CI 1.00–2.47) but not lower arm pain (OR 1.87; 95% CI 0.96–3.65) after adjusting for gender, age, body mass index, current daily smoking, heavy manual handling, and work with vibrating tools. Conclusions: Occupational cold exposure was statistically significantly associated with hand pain and upper arm pain. Therefore, occupational cold exposure should be recognized as a potential risk factor for musculoskeletal disorders in the upper extremity.